2019
DOI: 10.1136/jnnp-2019-320893
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Statin Treatment in Acute Ischaemic Stroke Patients with Intracranial Atherosclerosis: a High-Resolution Magnetic Resonance Imaging study (STAMINA-MRI Study)

Abstract: ObjectiveIntracranial atherosclerosis is a major cause of ischaemic stroke worldwide. A number of studies have shown the effects of statin treatment on coronary and carotid artery plaques, but there is little evidence on the effects of statin treatment on intracranial atherosclerotic plaques.MethodsThe Intensive Statin Treatment in Acute Ischaemic Stroke Patients with Intracranial Atherosclerosis - High-Resolution Magnetic Resonance Imaging (STAMINA-MRI) Trial is a single-arm, prospective, observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 51 publications
3
54
0
Order By: Relevance
“…Miao et al reported that the degree of stenosis in asymptomatic ICAS can be alleviated with intensive lipid-lowering therapy using statin for Chinese patients with asymptomatic ICAS (32). Chung et al found that high-dose statin treatment can significantly decrease the LDL-C levels and effectively stabilize symptomatic intracranial atherosclerotic plaques as documented by HR-MRI (33). Evidence above suggests that LDL-C may play a role in the formation and progression of ICAS, and maintaining LDL in a normal range may be the right choice for preventing ICAS in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Miao et al reported that the degree of stenosis in asymptomatic ICAS can be alleviated with intensive lipid-lowering therapy using statin for Chinese patients with asymptomatic ICAS (32). Chung et al found that high-dose statin treatment can significantly decrease the LDL-C levels and effectively stabilize symptomatic intracranial atherosclerotic plaques as documented by HR-MRI (33). Evidence above suggests that LDL-C may play a role in the formation and progression of ICAS, and maintaining LDL in a normal range may be the right choice for preventing ICAS in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…There have been few studies on lipid-lowering therapies that exclusively focus on ICAS. In a recent study, 55 the investigators enrolled statin-naïve patients with ischemic stroke who had symptomatic ICAS (>50% stenosis) in the proximal portion of the MCA, BA, or intracranial portion of the ICA. Atorvastatin (40 to 80 mg) or rosuvastatin (20 mg) was administered for 6 months, and patients underwent HR-MRI before and after statin treatment.…”
Section: Lipid-lowering Therapy In Patients With Intracranial Atherosclerosismentioning
confidence: 99%
“…These data suggest that diagnosis based solely on angiogram findings may not be accurate, which may explain why the effect of statins was not consistent in patients with ICAS. 55…”
Section: Lipid-lowering Therapy In Patients With Intracranial Atherosclerosismentioning
confidence: 99%
“…Since the hydrophilic group of statins is similar to the HMG portion of the substrate [3], statins can be used as competitive inhibitors of HMG-CoA. Therefore, statins can reduce cholesterol synthesis to prevent cardiovascular diseases such as atherosclerosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%